Factors associated with suicide after parasuicide in young people. Issue 6893 (19th June 1993) - Hawton, K; Fagg, J; Platt, S; Hawkins, M
Abstract : OBJECTIVE–To determine factors associated with completed suicide in young parasuicide patients. DESIGN–Case-control study. SETTING–Regional poisoning treatment centre in a teaching general hospital. SUBJECTS–Patients who, between 1968 and 1985 when aged 15-24 years, were admitted to the regional poisoning treatment centre because of deliberate self poisoning or self injury. Cases (n = 62) consisted of those who by the end of 1985 had died locally from either suicide (n = 41) or possible suicide (n = 21). Controls (n = 124) were patients who were known not to have died locally during the study period. Two controls were selected for each case, matched by sex, age (within two years), and length of follow up. MAIN OUTCOME MEASURES–Possible predictors of completed suicide. RESULTS–Univariate analysis (conditional logistic regression) showed that risk of death due to suicide and possible suicide was associated with six factors: social class V (odds ratio 2.7, 95% confidence interval 1.1 to 6.7), unemployment (2.8, 1.4 to 5.8), previous inpatient psychiatric treatment (4.9, 2.2 to 10.9), substance misuse (3.3, 1.6 to 6.8), personality disorder (2.1, 1.03 to 4.4), and previous attempted suicide (2.3, 1.2 to 4.4). Multivariate analysis identified two factors as significantly contributing to the model that best discriminated between the cases and controls: substance misuse (alcohol or drugs, or both) (adjusted odds ratio 3.9) and previous inpatient psychiatric treatment (3.7). These factors seemed to be associated with suicide after attempted suicide in both the short term (less than 12 months) and the long term (one year or more) and were also identified when the analysis was restricted to subjects who definitely died by suicide and their controls. CONCLUSIONS–Suicide after parasuicide in young people is associated with substance misuse. This suggests that prevention of suicide in young people who attempt suicide might be improved by close liaison between general hospital services for patients who have attempted suicide and services for young substance misusers and by measures aimed at preventing substance misuse in young people.